2020
DOI: 10.1177/1420326x19891761
|View full text |Cite
|
Sign up to set email alerts
|

Effect of solar radiation on human thermal comfort in a tropical climate

Abstract: The contribution of solar radiation on the global thermal comfort and local thermal comfort condition for a person sitting near a glass window in a building located in a tropical climate was studied. The effects of transmitted direct solar radiation, transmitted diffuse solar radiation, inside glass surface temperature and distance of a seated person from the glass window on the predicted percentage of dissatisfied (PPD) and plane radiant temperature asymmetry (RTA) were studied. PPD and RTA due to transmitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…This low indoor temperature obtained by the PMV-based controller is due to the high direct solar heat gains acquired through the windows during the winter. Indeed, these direct solar heat gains could affect the indoor thermal comfort levels, 48 and require cooling to maintain the PPD index at 5%. The extra cooling energy demand by the PMV-based controls compared to the temperature-based controls is depicted clearly in Figure 8(a).…”
Section: Influence Of the Walls' R-valuementioning
confidence: 99%
“…This low indoor temperature obtained by the PMV-based controller is due to the high direct solar heat gains acquired through the windows during the winter. Indeed, these direct solar heat gains could affect the indoor thermal comfort levels, 48 and require cooling to maintain the PPD index at 5%. The extra cooling energy demand by the PMV-based controls compared to the temperature-based controls is depicted clearly in Figure 8(a).…”
Section: Influence Of the Walls' R-valuementioning
confidence: 99%
“…Mirzabeigi et al 21 demonstrated that wet bulb globe temperature (WBGT) can be used as a thermal stress index to assess the effect of indoor direct solar radiation on occupants' thermal comfort by calculating ΔWBGT. Chaiyapinunt et al 22 investigated and analyzed the impact of solar radiation on the overall thermal comfort and local thermal comfort conditions of people sitting near glass windows in tropical climate buildings, using predicted percentage dissatisfaction (PPD) and planar radiation temperature asymmetry (RTA) as primary indicators.…”
Section: Introductionmentioning
confidence: 99%
“…At extremely high ambient temperatures and upon sun exposure, the maximum cabin temperature can reach 90 • C [9]. When the vehicle cabin interior temperature reaches a maximum of 45 • C, some components in the vehicle may deteriorate and damage [10,11]. Driving safety may be reduced owing to the reduction of driver alertness and component reliability caused by high temperatures.…”
Section: Introduction 1environment Inside Vehicles Exposed To Solar R...mentioning
confidence: 99%